Death and the Spectacle in Television and Social Media. (January 2020) - Stratton, Jon
Social media are pervaded by death. This article utilizes ideas drawn primarily from the work of Guy Debord—the society of the spectacle—and Jean Baudrillard—his discussion of death in Symbolic Exchange and Death, to think through the significance of death on social media. Debord argued that the consequence of the ubiquity of the mass media, and television in particular, and their increasing imbrication with consumption capitalism, was that social relations are increasingly lived as spectacle. At the same time, in the modern world, death has become increasingly separated from life. No longer integrated into social life, death has become the feared and meaningless end of life, which is to be preserved at all costs. The death that is now meaningful is not "natural" death but violent death. Social media is full of unnatural deaths including beheadings and suicide. This article discusses the pervasiveness of these on social media.